A Prospective Observational Study on Drug Utilisation Pattern of Restricted Antibiotics: Colistin, Teicoplanin and Tigecycline in a Tertiary Care Hospital - Varghese, Sophiya Thomas; Surendran, Lekshmi; Antony, Chinnu; Selvaraj, Hemalatha; Varghese, Emilda; Sherief, Sheik Haja; Sivakumar, Thangavel (Indian Journal of Pharmacy Practice)
Introduction: The emergence of antimicrobial resistance is a global threat. Now micro- organisms manage to overcome the antibiotics via various resistance mechanisms. This study was carried out to evaluate the appropriate usage and resistance pattern of the restricted antibiotics. Methods: A prospective observational study on Drug Utilization Pattern of Colistin, Teicoplanin and Tigecycline were conducted during the period of February 2016 – July 2016 at G. Kuppusamy Naidu Memorial Hospital, coimbatore, Tamil Nadu. Results: Out of 103 patients, 55 patients were treated empirically and 48 were treated based on their culture report. The antibiotics were prescribed mostly for patients with positive culture report followed by neutropenia patients and De-escalation was done only in 14 cases. The antibiotics were mostly consumed by patients in oncology department. On calculating the defined daily dose (DDD) Colistin was used predominantly, followed by teicoplanin and tigecycline. Conclusion: A stewardship Program must be implemented in the hospital to improve overall antibiotic usage in hospital. By this, we could reduce the emergence of antibiotic resistance up to a certain extent, by implementing a restricted antibiotic order form and proper follow up could add up to reduced antibiotic consumption.
Keywords: Drug use evaluation; Restricted antibiotics; Colistin; Teicoplanin; Tigecycline; Defined daily dose; Restricted antibiotic form